The Egoism and Altruism in Plato’s Philosophy: the Context and the Meaning - بلخن جناة (Milev Journal of Research and Studies, 2023)
The question of the identity and altruism is the most crucial issue in the modern philosophy. Nevertheless, this question is an old issue, which was deeply mused on, in ancient Greek philosophy. Thus, the present article is targeting at underscoring the early outset of the dialectic identity-altruism. To do so, we have been impelled to refer to Plato’s philosophy, who was the pioneer to discuss this question; he dealt with it under another dialectic: egoism-altruism. In fact, Plato referred to that dialectic while debating with Parmenides the dialectic of the existence-non-existence; that debate gave birth to the dialectic egoism-altruism or as it is known nowadays: identity-altruism. This article is meant to answer the following problematic: in which context did Plato use the dualism egoism-altruism? Was it a single context or interdisciplinary context? What was its meaning in each context? To deal with the above problematic, we combined in this article two approaches: an analytical approach to investigate the perspective and the position of Plato, and the comparative approach in order to compare Plato’s view to other view.